A new approach to video security over networks. (16th January 2006) - Memon, Qurban A.
A number of approaches currently used for video security have certain implementation specific problems in addition to being security deficient. The problems include computational power, memory requirement and/or dependence on existing compression algorithms. In this paper, we propose a combination of two approaches: a multiresolution transform with an additional feature of signal hopping; and use of synchronised chaos for information signals. The second method utilises chaos theory for encryption of the signals in networked environment. What is more, the approaches can be combined to provide a relatively higher degree of security with an ease of implementation for embedding in existing video compression algorithms. Both of these approaches are independent of any video compression algorithm. Detailed discussions are given to highlight implementation issues with respect to either of the approaches. We compare both approaches for the same purpose and propose some suggestions for implementation for various video applications.